FreeBSD 6 unleashed - Tiemann, Brian (Sams, 2006)
FreeBSD is extremely robust and powers some of the largest internet sites in world including Yahoo!. FreeBSD 6 Unleashed provides complete coverage of everything you need to know to use FreeBSD to its full potential, including coverage of FreeBSD 6.0. This edition includes updated coverage of Apache, MySQL and Sendmail, as well as added coverage of PowerPC support for Macintosh G3 and G4 platforms. This will be the most up to date, comprehensive reference on the market covering FreeBSD 6.0.